Physical sensors for skin‐inspired electronics. Issue 1 (3rd December 2019) - Li, Shuo; Zhang, Yong; Wang, Yiliang; Xia, Kailun; Yin, Zhe; Wang, Huimin; Zhang, Mingchao; Liang, Xiaoping; Lu, Haojie; Zhu, Mengjia; Wang, Haomin; Shen, Xinyi; et al.
Abstract: Skin, the largest organ in the human body, is sensitive to external stimuli. In recent years, an increasing number of skin‐inspired electronics, including wearable electronics, implantable electronics, and electronic skin, have been developed because of their broad applications in healthcare and robotics. Physical sensors are one of the key building blocks of skin‐inspired electronics. Typical physical sensors include mechanical sensors, temperature sensors, humidity sensors, electrophysiological sensors, and so on. In this review, we systematically review the latest advances of skin‐inspired mechanical sensors, temperature sensors, and humidity sensors. The working mechanisms, key materials, device structures, and performance of various physical sensors are summarized and discussed in detail. Their applications in health monitoring, human disease diagnosis and treatment, and intelligent robots are reviewed. In addition, several novel properties of skin‐inspired physical sensors such as versatility, self‐healability, and implantability are introduced. Finally, the existing challenges and future perspectives of physical sensors for practical applications are discussed and proposed. Abstract :